Health technology assessment: history and demand. - Stevens, A; Milne, R; Burls, A (2003)
Health technology assessment (HTA)--the provision to decision makers of information on the value of treatments and tests--has come of age in the last two decades. But it has deep roots in health care, with notable landmarks in (1) the mid eighteenth-century development of empiricism, (2) the twentieth century interest in outcomes and variation in health care, and (3) the pioneering work of Archie Cochrane and others in the 1970s. Three main forces have driven the recent developments of HTA: a combination of concerns about the adoption of unproven technologies, rising costs, and an inexorable rise in consumer expectations. The HTA response, essentially initiatives supporting the provision of reliable synthesised research information on the effects and costs of health technologies, have been well supported in the United Kingdom and internationally. We can be sure that HTA is here to stay.